Fecal Microbiota Transplantation is Safe and Efficacious for Recurrent or Refractory Clostridium difficile Infection in Patients with Inflammatory Bowel Disease. Issue 10 (October 2016) - Fischer, Monika; Kao, Dina; Kelly, Colleen; Kuchipudi, Aishwarya; Jafri, Syed-Mohammed; Blumenkehl, Mark; Rex, Douglas; Mellow, Mark; Kaur, Nirmal; Sokol, Harry; Cook, Gwen; Hamilton, Matthew J.; et al.
Abstract : Background: New treatments are needed as Clostridium difficile infection (CDI) is becoming increasingly formidable. Fecal microbiota transplantation (FMT) has a 90% success rate in the treatment of recurrent CDI. However, evidence regarding its safety, efficacy, and effect on disease activity in patients with inflammatory bowel disease (IBD) is lacking. Methods: This cohort study used data from 8 national and international academic centers. Patients with established IBD who underwent FMT for recurrent CDI were followed for a minimum of 3 months. The primary outcome was CDI recurrence at 3 months after FMT. The secondary outcomes were (1) IBD activity and severity at 3 months based on the judgment of the treating physician, endoscopic findings, and clinical disease activity scores; and (2) safety. Results: Sixty-seven patients were included in the analysis. Thirty-five (52%) had Crohn's disease, 31 (46%) ulcerative colitis, and one indeterminate colitis with 43 (64%) patients on an immunosuppressive agent at the time of FMT. The initial FMT was successful in 53 (79%) patients. After the FMT, IBD disease activity was reported as improved in 25 (37%), no change in 20 (30%), and worse in 9 (13%) patients. Serious adverse events included colectomy (1.4%), hospitalization for CDI (2.9%), hospitalization for IBD flare (2.9%), small bowel obstruction (1.4%), CMV colitis (1.4%), and pancreatitis (1.4%). Discussion: The overall CDI cure rates were high, with a large percentage of patients experiencing clinical improvement of their IBD after FMT. A minority of patients developed an IBD flare. No severe adverse events directly attributable to FMT were found in this largest reported series of recurrent or refractory CDI patients with concurrent IBD. Abstract : Article first published online 30 August 2016.